English in Performance - Marie Seux (Recherches)
Acting is playing. Learning by playing is therefore the challenge to take up when it comes to perfecting English through theatrical practice. But playing is not the only objective, because I add the four pillars of education, as defined by Unesco, to the game: 1- learning to know, 2- Learning to be, 3- Learning to do, 4- Learning to live together. The creation of a theatrical object in a foreign language goes hand in hand with learning to be a citizen by sharing knowledge and the indispensable collaborative work.